2021
DOI: 10.1021/acssynbio.1c00193
|View full text |Cite
|
Sign up to set email alerts
|

Automated Design of Robust Genetic Circuits: Structural Variants and Parameter Uncertainty

Abstract: Genetic design automation methods for combinational circuits often rely on standard algorithms from electronic design automation in their circuit synthesis and technology mapping. However, those algorithms are domain-specific and are hence often not directly suitable for the biological context. In this work we identify aspects of those algorithms that require domain-adaptation. We first demonstrate that enumerating structural variants for a given Boolean specification allows us to find better performing circui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 38 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…For example, the GDA tool Cello uses a circuit score based on the separation of the complementary Boolean outputs . It has been shown that the circuit topology plays an important role in genetic circuit design . Yet, the computationally challenging part of circuit design is finding an assignment of genetic gates from a library to the topology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the GDA tool Cello uses a circuit score based on the separation of the complementary Boolean outputs . It has been shown that the circuit topology plays an important role in genetic circuit design . Yet, the computationally challenging part of circuit design is finding an assignment of genetic gates from a library to the topology.…”
Section: Resultsmentioning
confidence: 99%
“… 25 It has been shown that the circuit topology plays an important role in genetic circuit design. 19 Yet, the computationally challenging part of circuit design is finding an assignment of genetic gates from a library to the topology. Each single assignment needs to be evaluated by simulating the circuit and determining its score, making the gate assignment a combinatorial optimization problem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cello then optimizes the modular construction of the logic circuit from a parts library to create a linear DNA sequence with the desired circuit. Another method ( 17 ) exhaustively explores fan-out free circuit structures and jointly optimizes structure and parts assignment for a specific logic function.…”
Section: Introductionmentioning
confidence: 99%